2017
DOI: 10.1080/15222055.2017.1334725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Optimum and Suboptimum Dietary Protein on Hemolymph Physiology, Oxidative Physiology, Plasma Fatty Acids, and Histoarchitectural Modulations in Farmed Giant Freshwater Prawns Macrobrachium rosenbergii

Abstract: We examined the effect of optimum (32%) and suboptimum (27%) levels of dietary protein on the hemolymph and oxidative physiology of giant freshwater prawn Macrobrachium rosenbergii juveniles. Wild juveniles of different stocks were collected from the west coast (Gujarat [G-stock] and Maharashtra [M-stock]) and east coast (Andhra Pradesh [A-stock]) of India. Prawns were raised in 200-m 2 culture ponds, with individual animals tracked by using stock-specific, colored elastomer tags. Hemolymph glucose, plasma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Borinson et al () showed a decrease in gills LDH activity in Leiostomus xanthurus in response to hypoxia. Consequently, lower gill LDH activity in stock “A” can be correlated with the gills pathological conditions (massive edema with atrophy and hemocyte infiltration) found in this stock (Sagar et al, ). Similarly, lower LDH gills recorded for M. rosenbergii fed SDP may be due to the stress of energy deficiency and, in turn, lower survival of this stock (Sagar et al, ).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Borinson et al () showed a decrease in gills LDH activity in Leiostomus xanthurus in response to hypoxia. Consequently, lower gill LDH activity in stock “A” can be correlated with the gills pathological conditions (massive edema with atrophy and hemocyte infiltration) found in this stock (Sagar et al, ). Similarly, lower LDH gills recorded for M. rosenbergii fed SDP may be due to the stress of energy deficiency and, in turn, lower survival of this stock (Sagar et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, although not significant, higher muscle LDH activity in optimum dietary protein fed M. rosenbergii can be correlated with their higher growth and survival than stock “A”’s growth and survival during the experimental period. We have demonstrated previously that optimum dietary protein (32%) fed M. rosenbergii achieves weight gain and higher specific growth rates of 95% and 80%, respectively in comparison to sub‐optimum dietary protein (27%) fed prawns (Sagar et al, ). In contrast, Manush et al () reported a gradual decrease in the hepatopancreatic LDH activity with increasing dietary protein level when prawns were stressed due to claw ablation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations